FINANCIAL FLOWS AND SOCIAL SUSTAINABILITY DEVELOPMENT IN NIGERIA - Mayowa Ebenezer ARIYIBI; James Ayanwale OBADEYI; Taofeek Osidero AGBATOGUN (Modern Management Review, 2025)
The three inter-related pillars of sustainable development have been neglected by the United Nation which informed examining the impact of financial flows on the attainment of quality education (Goal 4). The study employed time-series data sourced from Central Bank Statistical Bulletin and World Development Indicator from 1991 to 2022. The auto-regressive distributed lag was employed to determine the short and long-run relationship between the outcome and explanatory variables. The findings revealed that remittances and external debt had a positive significant effect on primary school enrolment rate, while government expenditure on education had a negative significant effect on primary school enrolment rate. It is therefore recommended that government should ensure transaction cost does reduce remittances and ensure external debt and government expenditure on education are expended to educational sector to improve primary school enrolment rate.